Patient-Reported Outcome Measures Used in Gender Confirmation Surgery: A Systematic Review. Issue 4 (April 2018) - Andréasson, My; Georgas, Konstantinos; Elander, Anna; Selvaggi, Gennaro
Abstract : Background: The usefulness of patient-reported outcome measures is emphasized along with the development of patient-centered care. When implementing patient-reported outcome measures, evidence of the instrument's validity, reliability, and responsiveness in the target population is necessary to secure accurate reporting of the patient's experience. The aim of this study was to identify the literature in which structured patient-reported outcome measures have been used to evaluate the results of gender confirmation surgery, and to systematically evaluate the validity of these instruments. Methods: A systematic review of the current literature was performed to identify structured patient-reported outcome measures used to evaluate the outcome of gender confirmation surgery. The identified instruments' validity in the transgender population was assessed for adherence to international guidelines for development and validation of health outcomes instruments. Results: A total of 110 instruments were identified: 64 ad hoc; six generic; 24 evaluating psychiatric, social, or psychosocial aspects; nine evaluating function but only valid in other patient groups; five ad hoc with some formal development/validation; and two specific for gender dysphoria. Conclusions: There is a lack of patient-reported outcome measures that are valid for the transgender population and concurrently sensitive enough to evaluate gender confirmation surgery without the influence of other gender confirming interventions. Basing research on instruments without confirmed validity decreases the validity of the study itself; thus, previous research using patient-reported outcome measures to evaluate gender confirmation surgery can be considered to have a low level of evidence. To obtain valid patient-reported outcome measures, specific for evaluating the results of gender confirmation surgery, development of new instruments or adaptation of existing instruments is needed. Abstract : Supplemental Digital Content is available in the text.